Emergency communications interoperability for disaster management : case study: Jordan - Alzaghal, Mohamad H. (Germany: LAP Lambert Academic Publishing, 2010)
Interoperable Emergency Communications: Recently, the world has been affected by man-made and natural disasters of a level not witnessed before which depicts the importance of communication for an efficient and rapid response of First Responder Community (FRC) members in the field. The resilience of communications infrastructure is vital for the well being of any country. It is essential to build a robust and interoperable Information and Communications Technology (ICT) infrastructure before the disaster, which will facilitate patch/restore/reconstruct it when and after the disaster hits. The author explored Jordan's current emergency communications interoperability plans, policies, Emergency Operation Plans (EOPs) and compares Jordan's HA/DR communications readiness level versus U.S.'s. Based on the technological aspects of emergency communications, Jordan's communications environment, the requirements analysis of emergency communications plan, and lessons learned from the U.S. experience, a proposed Jordan Emergency Communications Interoperability Plan (JECIP) is introduced in this book.
Keywords: Emergency; Disaster Management; Jordan